Digital Competence in teaching performance in a Primary level educational institution - Cotohuanca Cruz, Sujeidy María (2022)
Education has undergone tremendous changes, including providing a dynamic process between teachers and students. The purpose of this study was to determine the incidence of digital competence on teaching performance in primary level educational institutions. The quantitative approach was assumed, following a basic type of research, non-experimental design and cross-sectional level of causal description. The non-probabilistic sampling method was used, two questionnaires were administered to 85 elementary school teachers. The results were analyzed using ordinary linear regression statistics. To test the research hypotheses, a Nagelkerke R2 of 0.578 was obtained, which explains the variability in the data and identifies the effect of numerical skills on academic performance at 57.8%. A significance, p=0.000 representing that p is less than the significance value of 0.05, which means that the event is significant. It was concluded that digital skills have a significant impact on teaching performance in an elementary school.